2015
DOI: 10.1097/mao.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility in Noise With a Single-Unit Cochlear Implant Audio Processor

Abstract: The study indicates that CI users with the receiver/stimulator implanted in positions further behind the ear are expected to have higher difficulties in noisy situations when wearing the single-unit audio processor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
15
3
Order By: Relevance
“…Recently, an off-the-ear (OTE) sound processor for CIs was introduced which integrates the coil, processor and microphones into a single unit worn over the implant site (Mertens et al, 2015;Wimmer et al, 2015). This sound processor placement is very similar to the posterior auricular placement of bone conduction implants.…”
Section: Cochlear Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an off-the-ear (OTE) sound processor for CIs was introduced which integrates the coil, processor and microphones into a single unit worn over the implant site (Mertens et al, 2015;Wimmer et al, 2015). This sound processor placement is very similar to the posterior auricular placement of bone conduction implants.…”
Section: Cochlear Implantsmentioning
confidence: 99%
“…This is probably because the subjects were tested with the non-test ear un-occluded, meaning advantage provided by their normal-hearing ear would easily obscure any subtle differences that may have existed between the processors. Wimmer et al (2015) tested unilateral hearing performance with these same processors, but in subjects with profound bilateral hearing loss. In this study they found significantly poorer hearing performance with the OTE compared to the BTE sound processor when tested using a speech signal from the front and competing noise from the rear.…”
Section: Cochlear Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wimmer et al (13) measured the speech intelligibility in noise performance of experienced CI users in 4 spatial configuration with the Oldenburg sentence test. They compared the SRT performance between Rondo and Opus 2 system and found no statistically significant differences in the situations in which the signal came from the front and noise came from the frontal, ipsilateral and contralateral sides.…”
Section: Advantage Of the Directivity Of Cochlear Implantmentioning
confidence: 99%
“…Wimmer et al's article "Speech intelligibility in noise with a single-unit cochlear implant audio processor" [2] found that speech understanding in noise with the RONDO was only significantly worse than with the OPUS 2 when speech was presented from the front and noise from the back (the S 0 N 180 setting)-not when speech was presented from the front (S 0 N 0 ) of the sides (S 0 N IL and S 0 N CL ). Considering that our article did not specify the test setup we used for speech understanding in noise testing, it was inaccurate to assert that Wimmer et al's findings contradicted our own or those of Mertens et al [3] and Távora-Vieira and Miller [4] without considering test setup.…”
mentioning
confidence: 99%